Disaster Risk Management and Sustainability: Contributions from the Governance approach - Barberis, Matías; Fontana, Silvia E. (Estado, Gobierno y Gestión Pública, 2018)
This paper aims to analyze the role of governance in disaster risk management, starting from the local characteristics that emerge from the last floods in the province of Cordoba. Indeed, it intends to investigate the reality of the disasters from a conceptual point of view. The naturalization of the risks by the inhabitants causes that the governments do not incorporate hypotheses of the risk in their agendas, generating different shortcomings in terms of actions of prevention and mitigation of risks. In order to overcome this situation, governance and sustainability are key approaches in the design and implementation of efficient risk management policies.